Religious tolerance in celebration of religious (non-moeslem) holidays in Java and Bali: The Definition of Religious Tolerance, The Concept of Implementing Religious Tolerance in Celebrations of Holidays in Java and Bali, Boundaries in Religious Tolerance - Karomah, Maulidatul Lailatul (Maliki Interdisciplinary Journal, 2023)
Religious tolerance is an attitude of openness, mutual understanding and respect that must be possessed by every individual in establishing social interaction with people of other religions. This aims to create harmony between religious communities and prevent religious conflict and discrimination. Religious tolerance also involves understanding the culture of each religion. In a multicultural society, there are many kinds of politics, culture, and religion. This can lead to conflict due to conflicting interests. Religious tolerance is important to maintain social stability and prevent inter-religious conflict. Religious tolerance can be realized through an inclusive attitude, namely acknowledging the truth of one's own religion but still being open and respecting the truth of other religions. The application of religious tolerance in Java and Bali has a different historical context. Islam first arrived in Java in the 13th century through trade routes with Muslim traders. Trade interactions and marriages between Muslim traders and local residents played an important role in the spread of Islam in Java. In Bali, the influence of Islam is not as big as in Java, because Bali is still dominated by Hinduism. Nonetheless, traces of Islam can be found in several aspects of culture, art, and architecture in Bali.